2020
DOI: 10.3889/oamjms.2020.3482
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Tests of N-hexane, Ethyl Acetate, and Methanol Leaves (Vitex) Extract (pinnata) against Streptococcus mutans

Abstract: BACKGROUND: Vitex pinnata is known as Laban, which is a medicinal plant used traditionally for generations to generations. Laban leaf extract with various concentrations has antibacterial activity. Laban leaf extract is known to inhibit the formation of Streptococcus mutant in human teeth. AIM: To exam, the minimum inhibitory concentration (MIC) and minimum kill concentration (KBM) extract Laban leaves (V. pinnata) as an antibacterial against Streptococcus mutants. METHODS: This research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Table 2 shows that ethanol extract and methanol extract can kill S. aureus bacteria at a concentration of 64%, while the N-Hexane extract has not been able to kill bacteria. Ethanol and methanol extracts have a faster killing ability at smaller concentrations than N-Hexane extracts [21] [5]. Staphylococcus aureus is a Gram-positive bacterium, where the cell wall component is polar, while N-Hexane is non-polar.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows that ethanol extract and methanol extract can kill S. aureus bacteria at a concentration of 64%, while the N-Hexane extract has not been able to kill bacteria. Ethanol and methanol extracts have a faster killing ability at smaller concentrations than N-Hexane extracts [21] [5]. Staphylococcus aureus is a Gram-positive bacterium, where the cell wall component is polar, while N-Hexane is non-polar.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a new class of antibiotics had not been developed for over three decades [1]. Research on antimicrobial substances using natural resources has become a serious discussion by researchers [2][3][4][5][6][7][8][9][10][11][12]. The utilization of plant secondary metabolites to cure various illnesses was an ancient practice of taking the resources available in markets, gardens, horticulture backyards, and areas with pristine vegetation [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is even more popular nowadays because of the advantages of the natural product compared to synthetic material in offering safer, low side effects and green chemistry [7] materials. Many research reported either by in-silico [8,9] or invivo that the natural product from the plant contains various medical activities to be antimicrobial [10], antiviral [11], antibacterial [12][13][14], antibiofilm [15], antioxidant [16,17], and so on.…”
Section: Introductionmentioning
confidence: 99%